2016
DOI: 10.18805/ijar.11424
|View full text |Cite
|
Sign up to set email alerts
|

Study on epidemiological trends of canine rabies between2011 and 2014 in Chennai city, South India

Abstract: The objective of present study was to identify various epidemiological factors associated with canine rabies in Chennai city. Data were collected from a total of 169 canine rabies suspected cases which included, retrospective data of 102 (September 2011 to March 2013 and prospective data of 67 that were collected from Under Observation for Rabies (UOR) ward, Teaching Hospital, Madras Veterinary College. The data compiled over 3 years from 169 suspected canine rabid animals were analyzed based on Seller's stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This could be due to greater interaction of this age group with dogs either as pets.A large proportion of dog bite victims were students (33.97%) followed by unskilled groups (30.08%) ( Table 1) again indicating their epidemiological study by (Suraweera et al, 2012) reported 24.3%. Highest victims of dog bites were reported from central part of Chennai as possibly this part Chennai is known to have more number of rabies suspected dogs compared to other parts (Figure 1) which is correlated to the spatial distribution of canine rabies in Chennai city (Figure 2) (Bharathy and Gunaseelan, 2016). Hence people in these areas may be considered to be at a higher risk for dog bites.…”
Section: Resultsmentioning
confidence: 86%
“…This could be due to greater interaction of this age group with dogs either as pets.A large proportion of dog bite victims were students (33.97%) followed by unskilled groups (30.08%) ( Table 1) again indicating their epidemiological study by (Suraweera et al, 2012) reported 24.3%. Highest victims of dog bites were reported from central part of Chennai as possibly this part Chennai is known to have more number of rabies suspected dogs compared to other parts (Figure 1) which is correlated to the spatial distribution of canine rabies in Chennai city (Figure 2) (Bharathy and Gunaseelan, 2016). Hence people in these areas may be considered to be at a higher risk for dog bites.…”
Section: Resultsmentioning
confidence: 86%
“…India is endemic for rabies bearing an annual burden of 35 per cent of the world's human mortality most of which is canine-mediated (W HO, 2018; Bharathy and Gunaseelan, 2016). Except for RABV, no other lyssaviruses have been reported from India (WHO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…. An epidemiologial survey in Chennai, India shows that Rabies is endemic in India(Bharathy and Gunaseelan 2016). Rabies virion, is a bullet shaped, enveloped infectious particle (180 nm x 75 nm in size), having 12 Kb negative sense single-stranded RNA genome, belonging to the Lyssavirus genus of the Rhabdoviridae family and Mononegavirale order.…”
mentioning
confidence: 99%